Mengungkap Realitas Stunting Di Desa Karya Mulya: Tantangan Dan Solusi - Asiah Wasillah; Hamdani Fadila; Muhammad Rifqi Aditama; Alvin Nasri; Melinda Rizkhi; Cahaya Eka Juniarti; Fitri Auliya Rahmi; Ildri Maysah Murni; Ninong Putri; Erma Putriyani (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2023)
Stunting is a condition in which a child's weight and height are significantly below that of their peers of the same age, and it becomes noticeable when a child reaches the age of two. Stunting can be attributed to several interconnected factors such as genetics, economic conditions, household circumstances, parenting styles, insufficient nutritional intake, limited access to healthcare services, clean water scarcity, and inadequate sanitation. Stunting remains a paramount issue in terms of nutrition and health in Indonesia, including in the Riau region. Rambah Sambo sub-district is one of the seven sub-districts in Rokan Hulu Regency that has villages with a stunting locus status, and one of them is Karya Mulya Village. To shed light on the reality of stunting in the Riau Province, the University of Riau 2023 Community Service (Kukerta) Team in Karya Mulya Village will conduct observations and interviews with the local community to gauge their understanding and knowledge regarding this stunting issue. Most community members or parents with stunted children generally do not comprehend the meaning of stunting itself. However, based on observations, the knowledge of Karya Mulya Village residents about stunting falls into the "adequate" category, leaving them to speculate about it. Some respondents refer to stunting as malnutrition and prefer to describe it as a lack of height. Some of the Karya Mulya Village residents have grasped the consequences or effects of stunting on a child's future. The majority of the community agrees that stunting can disrupt a child's mental health. In preventing and reducing stunting cases, Karya Mulya Village faces several challenges. The first is changing community behaviors, and the second pertains to improving nutrition and food, as there are still community members who do not provide high-protein and nutritious food to their children.